RIWAYAT IMUNISASI DAN KONSUMSI GIZI RUMAH TANGGA SEBAGAI FAKTOR RISIKO STUNTING PADA MASYARAKAT PERBATASAN KOTA DI KABUPATEN KUBU RAYA - Harzuna, Amanda; Trisnawati, Elly; Budiastutik, Indah (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background : Stunting remains a significant public health problem in Indonesia, particularly in Kubu Raya Regency, which had the highest stunting prevalence in West Kalimantan at 40.35% in 2021. This study aimed to analyze the influence of complete basic immunization history and household nutritional consumption on stunting incidence among children under five. Method : The research employed a case-control design with a sample of 120 children under five, consisting of 60 stunted children (cases) and 60 normal children (controls) in Mega Timur and Sungai Malaya Villages, Sungai Ambawang District. Data collection used random sampling technique and data analysis used chi-square test. Results: The results showed significant relationships between complete basic immunization history (p=0.015; OR=2.704) and household nutritional consumption (p=0.040; OR=2.333) with stunting incidence. Children with incomplete immunization history had 2.7 times greater risk of experiencing stunting, while children from food-insecure households had 2.3 times greater risk of stunting. Conclusion: Basic immunization history and household nutritional consumption were identified as contributing factors to stunting incidence among under-five children. The study findings revealed significant associations between complete basic immunization history (p=0.015; OR=2.704) and household nutritional consumption (p=0.040; OR=2.333) with stunting risk in under-five children. Keywords: Food Expenditure Blood glucose, Immunization, Nutrition, Stunting.